The Effect of Teacher Characteristics, Education Policy and School Quality on School Effectiveness and High School Student Performance in Sukabumi - Syafruddin; Sudadi; Muhamad Ahyat; Rochmi Hastuti (Jurnal Pendidikan West Science, 2023)
This study examined the influence of teacher characteristics, education policies, and school quality on school effectiveness and high school student performance in Sukabumi. This study used a survey design and collected data from 300 teachers in 30 high schools in Sukabumi. The data were analyzed using structural equation modeling with SmartPLS. The results showed that teacher characteristics, education policies, and school quality had a significant positive impact on school effectiveness and high school student achievement. The study concludes that policies aimed at improving the quality of education, such as improving access to educational resources and providing teacher training programs, have a positive impact on school effectiveness.